Preparation method of heat insulation reinforcing material for mine roadway guniting support

By using spray support materials made of cotton straw and other materials, the problem of insufficient insulation and mechanical properties in the prior art is solved, better insulation and reinforcement effects are achieved, and the safety and reliability of mine tunnel support is significantly improved.

CN119504195APending Publication Date: 2025-02-25SHANDONG GOLD MINE CO LTD XINCHENG GOLD MINE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411691175.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing mine tunnel support technology has problems with insufficient thermal insulation and mechanical properties, especially in high-temperature surrounding rock environments, which leads to poor mechanical properties and durability of concrete-enclosed rocks, which are prone to cracks and affects the support effect.

Method used

The spray support material made of cotton straw, slag powder, fly ash, Na2SiO3 and NaOH is used. Through solid-liquid mixing and stirring, quartz sand, aluminum powder foaming agent and foam stabilizing agent are added to form a material with good heat insulation and reinforcement effect.

Benefits of technology

It significantly improves the thermal insulation and mechanical properties of the mine tunnel spray support material, reduces the thermal conductivity, enhances the compressive strength, improves the strength and toughness of the material, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504195A_ABST
    Figure CN119504195A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a heat-insulation reinforcing material for mine roadway guniting support. The preparation method comprises the following steps: crushing cotton straws, sieving, and drying until the mass is constant; the preparation method comprises the following steps: preparing an alkali activator solution formed by mixing NaOH and Na2SiO3; mixing and stirring slag powder and fly ash to obtain a slag-ash mixture; then carrying out solid-liquid mixing on the slag-ash mixture and an alkali activator solution, and adding 2-5% of quartz sand; after stirring, sequentially adding 20 to 28 percent of cotton straw, 0.35 to 0.45 percent of aluminum powder foaming agent and a proper amount of foam stabilizer; the water-cement ratio of the thermal insulation reinforcing material is (0.4-0.6): 1. The thermal insulation reinforcing material is used for shotcrete support of the mine laneway. According to the invention, light materials such as cotton straws are added, so that the guniting support material has better heat preservation and heat insulation effects. The cotton straw can also effectively prevent the expansion of internal cracks, and can better improve the strength and toughness of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mine tunnel support, and in particular relates to a method for preparing a heat-insulating reinforcement material for mine tunnel shotcrete support. Background Art

[0002] In recent years, as shallow resources in my country have gradually dried up, mines have gradually entered the stage of deep mining. Mine temperature and heat damage have become one of the major issues restricting mine safety production. These problems seriously affect the construction efficiency and physical and mental health of underground workers, and are likely to cause various diseases and lead to complex accidents underground. In addition, most underground projects use shotcrete for stacking support. Due to the effect of high-temperature surrounding rock, stress concentration is prone to occur at the contact surface between rock and concrete, resulting in poor mechanical properties and durability of concrete-surrounding rock, and cracks are prone to occur, which greatly reduces the support effect and poses a great threat to mine safety production and daily management. Therefore, in view of the problems existing in the existing mine tunnel support technology, it is of great significance to propose a new type of thermal insulation reinforcement material for mine tunnel shotcrete support. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing a thermal insulation reinforcement material for mine tunnel shotcrete support, so as to further improve the thermal insulation performance and mechanical properties of the mine tunnel shotcrete support material.

[0004] The technical solution of the present invention is as follows: A preparation method of a thermal insulation reinforcement material for shotcrete support of a mine tunnel is prepared according to the following steps: first, crushing and screening cotton stalks, drying them to a constant mass, and bagging them for later use; and preparing an alkali activator solution formed by mixing a NaOH solution and Na2SiO3; and mixing slag powder and fly ash to obtain a slag-ash mixture; secondly, performing solid-liquid mixing on the slag-ash mixture and the alkali activator solution, and adding quartz sand accounting for 2-5% of the total mass of the solid-liquid mixture after the solid-liquid mixing; and adding cotton stalks accounting for 20-28% of the total mass of the solid-liquid mixture, an aluminum powder foaming agent accounting for 0.35-0.45% of the total mass of the solid-liquid mixture, and an appropriate amount of a foam stabilizer in sequence after stirring; and preparing the thermal insulation reinforcement material for shotcrete support of a mine tunnel with a water-cement ratio of (0.4-0.6):1 under stirring; the mass ratio of the slag-ash mixture to the alkali activator solution in the solid-liquid mixture is (5-7):1.

[0005] Preferably, the amount of cotton straw added is 24% of the total mass of the solid-liquid mixture.

[0006] Preferably, the amount of aluminum powder foaming agent added is 0.4% of the total mass of the solid-liquid mixture.

[0007] Preferably, the mass ratio of slag powder to fly ash is (6-8):3.

[0008] Preferably, the alkaline activator solution is prepared as follows: 2% NaOH solution and Na2SiO3 are uniformly mixed to obtain an alkaline activator solution; the mass ratio of NaOH solution to solid Na2SiO3 is (0.5~1.5):1.

[0009] Preferably, the foam stabilizer is potassium stearate; the added amount is (0.04-0.06) of the total mass of the solid-liquid mixture.

[0010] Preferably, the quartz sand has a particle size of 1-4 mm.

[0011] The present invention mainly uses industrial waste slag and fly ash as raw materials, Na2SiO3 and NaOH as alkali activators, quartz sand as filling aggregate, cotton straw as insulation material and reinforcing agent, aluminum powder as foaming material, and potassium stearate as foam stabilizer to prepare a thermal insulation reinforcement material for mine tunnel shotcrete support. Among them, slag can be obtained by water extraction of molten slag on the surface of molten iron in the ironmaking process, and is a grayish white powder. Fly ash is mainly fine ash captured from the flue gas after coal combustion, and is a common solid waste in factories. The material is sprayed onto the surface of the tunnel surrounding rock through the shotcrete support method, which not only effectively blocks the heat release of the surrounding rock to the mine tunnel, but also plays a role in reinforcing and supporting the surrounding rock.

[0012] Compared with the prior art, the present invention has the following characteristics: First, the present invention uses waste slag and fly ash generated by industrial production as raw materials for preparation, which is conducive to promoting the resource utilization of solid waste, reducing environmental pollution, and has significant environmental, social and economic benefits.

[0013] Second, the present invention adds light materials such as cotton straw to make the shotcrete support material have better thermal insulation effect. In addition, cotton straw can effectively prevent the expansion of internal cracks, and can better improve the strength and toughness of the material. In particular, the present invention combines multiple materials in a synergistic way, and more uniform and closed pores can be formed in the material, so that the thermal conductivity of the material can be significantly reduced.

[0014] Third, the shotcrete support material prepared by the present invention overcomes the defects of traditional concrete such as heavy weight, poor durability, and poor thermal conductivity. It has the advantages of wide source of raw materials, simple preparation process, low carbon emissions, high strength and durability, and good thermal insulation performance, and has a very broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a comparison chart of uniaxial compressive strength and thermal conductivity data obtained by testing various embodiments of the present invention. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with embodiments and comparative experimental data.

[0017] The sodium silicate selected in the present invention is a quick-dissolving sodium silicate powder with a modulus of 2.0 and a net content of ≥75%. The selected NaOH is in solid granular form with a purity of ≥75%. The selected quartz sand has a Mohs hardness of 7, a porosity of 43%, and a SiO2 content of >99.6%. The selected aluminum powder foaming agent is in powder form with an active aluminum content of >80%. The selected foam stabilizer is potassium stearate. Example 1

[0018] Step 1: Wash the cotton straw with tap water and dry it naturally, then put the dried cotton straw into a high-speed crusher to reduce the particle size of the cotton straw and increase its surface area. The crushed straw residue is passed through a 4-mesh sample sieve and placed in a drying oven at 80°C to dry until the mass is constant, and then bagged for later use.

[0019] Step 2: Weigh a certain amount of slag powder and fly ash, mix them in a mass ratio of 7:3, and add them into a stirring kettle. Stir at 200r / min for 3min, and then stir at 400r / min for 2min to mix the slag powder and fly ash powder evenly to obtain a slag ash mixture.

[0020] Step 3: Prepare 2% NaOH solution, place it in a beaker, seal it with plastic wrap, and leave it at room temperature for 24 hours. Take an appropriate amount of 2% NaOH solution, add Na2SiO3 to it, and prepare an alkaline activator solution according to the mass ratio of NaOH solution to solid Na2SiO3 of 1:1.

[0021] Step 4: Mix the prepared slag ash mixture with the alkaline activator solution in a mass ratio of 6:1. After the solid-liquid mixture, add quartz sand with a particle size of 1-2mm and quartz sand with a particle size of 2-4mm, which accounts for 5% of the total mass of the solid-liquid mixture, and stir at 300r / min for 3min. Then add cotton straw with a total mass of 0% of the solid-liquid mixture, aluminum powder foaming agent with a total mass of 0.3% of the solid-liquid mixture, and foam stabilizer with a total mass of 0.05% of the solid-liquid mixture, and stir at 500r / min for 10min. The water-cement ratio is configured to be a thermal insulation reinforcement material for mine tunnel shotcrete support with a water-cement ratio of 0.5.

[0022] Step 5: After the mixing is completed, pour the prepared sample into the cement curing mold immediately. The slurry is loaded into the test mold twice, and each time it is placed on the vibration table for full vibration. After the sample is formed, cover it with plastic wrap and cure it in a standard curing box with a temperature of 30±0.5℃ and a humidity of 95% for 3 days.

[0023] Step 6: After the curing is completed, refer to DZ / T 0276.18 "Test Procedure for Physical and Mechanical Properties of Rock Part 18 Uniaxial Compressive Strength Test of Rock" and JGJ 51-2002 "Technical Specification for Lightweight Aggregate Concrete" to carry out the measurement of uniaxial compressive strength and thermal conductivity parameters of the test blocks, and evaluate the strength and thermal insulation effect of the thermal insulation reinforcement materials used for shotcrete support of mine tunnels.

[0024] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 1 is 8.1Mpa, and the thermal conductivity is 0.863w (m﹒k) -1 . Example 2

[0025] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 12% and 0.3% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0026] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 2 is 13.6Mpa, and the thermal conductivity is 0.322w (m﹒k) -1 . Example 3

[0027] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 24% and 0.3% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0028] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 3 is 14.3Mpa, and the thermal conductivity is 0.238w (m﹒k) -1 . Example 4

[0029] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 36% and 0.3% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0030] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 4 is 12.8Mpa, and the thermal conductivity is 0.421w (m﹒k) -1 . Example 5

[0031] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 0% and 0.4% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0032] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 5 is 9.8Mpa, and the thermal conductivity is 0.798w (m﹒k) -1 . Example 6

[0033] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 12% and 0.4% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0034] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 6 is 14.9Mpa, and the thermal conductivity is 0.289w (m﹒k) -1 . Example 7

[0035] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 24% and 0.4% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0036] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 7 is 15.5Mpa, and the thermal conductivity is 0.212w (m﹒k) -1 . Example 8

[0037] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 36% and 0.4% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0038] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 8 is 13.4Mpa, and the thermal conductivity is 0.375w (m﹒k) -1 . Example 9

[0039] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 0% and 0.5% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0040] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 9 is 7.5Mpa, and the thermal conductivity is 0.896w (m﹒k) -1 . Example 10

[0041] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 12% and 0.5% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0042] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 10 is 12.5Mpa, and the thermal conductivity is 0.384w (m﹒k) -1 . Embodiment 11

[0043] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 24% and 0.5% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0044] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 11 is 13.8Mpa, and the thermal conductivity is 0.249w (m﹒k) -1 . Example 12

[0045] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 36% and 0.5% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0046] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 12 is 11.6Mpa, and the thermal conductivity is 0.498w (m﹒k) -1 . Embodiment 13

[0047] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 0% and 0.6% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0048] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 13 is 6.4Mpa, and the thermal conductivity is 0.999w (m﹒k) -1 . Embodiment 14

[0049] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 12% and 0.6% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0050] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 14 is 11.7Mpa, and the thermal conductivity is 0.401w (m﹒k) -1 . Embodiment 15

[0051] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 24% and 0.6% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0052] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 15 is 12.3Mpa, and the thermal conductivity is 0.262w (m﹒k) -1 . Example 16

[0053] In the fourth step, the amounts of cotton straw and aluminum powder foaming agent added are 36% and 0.6% of the total mass of the solid-liquid mixture, respectively, and the rest are the same as in Example 1.

[0054] The test results show that the uniaxial compressive strength of the thermal insulation reinforcement material for mine tunnel shotcrete support under the formula of Example 16 is 10.5Mpa, and the thermal conductivity is 0.552w (m﹒k) -1 . Experimental results analysis:

[0055] In the above embodiments, Examples 1, 5, 9, and 13 did not add straw. Examples 2, 6, 10, and 14 added 12% straw. Examples 3, 7, 11, and 15 added 24% straw. Examples 4, 8, 12, and 16 added 36% straw.

[0056] Example 1-4 Aluminum powder 0.3%. Example 5-8 Aluminum powder 0.4%. Example 9-12 Aluminum powder 0.5%. Example 13-16 Aluminum powder 0.6%.

[0057] The following combination Figure 1 Analyze the experimental results.

[0058] 1. Adding straw significantly improves the compressive strength. However, adding too much or too little is not conducive to effectively improving the compressive strength.

[0059] For example, when comparing Examples 2 and 3, it can be seen that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 12%. When comparing Examples 3 and 4, it can be seen that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 36%.

[0060] For another example, a comparison between Examples 6 and 7 shows that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 12%. A comparison between Examples 7 and 8 shows that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 36%.

[0061] For another example, a comparison between Examples 10 and 11 shows that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 12%. A comparison between Examples 15 and 16 shows that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 36%.

[0062] For another example, a comparison between Examples 14 and 15 shows that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 12%. A comparison between Examples 11 and 12 shows that when the amount of aluminum powder added is the same, the compressive strength of the straw added at 24% is higher than that of the straw added at 36%.

[0063] 2. Adding different amounts of aluminum powder foaming agent and 0.05% foam stabilizer has different effects on reducing thermal conductivity.

[0064] For example, when 12% of straw is added, the amount of aluminum powder added in Examples 2, 6, 10, and 14 is 0.3%, 0.4%, 0.5%, and 0.6%, respectively, and the corresponding thermal conductivity is 0.322w (m﹒k) respectively. -1 、0.289w(m﹒k) -1 、0.384w(m﹒k) -1 and 0.401w(m﹒k) -1 .

[0065] For another example, when 24% of straw is added, the amount of aluminum powder added in Examples 3, 7, 11, and 15 is 0.3%, 0.4%, 0.5%, and 0.6%, respectively, and the corresponding thermal conductivity is 0.238w (m﹒k) respectively. -1 、0.212w(m﹒k) -1 、0.249w(m﹒k) -1 and 0.262w(m﹒k) -1 .

[0066] For another example, when 36% of straw is added, the amount of aluminum powder added in Examples 4, 8, 12, and 16 is 0.3%, 0.4%, 0.5%, and 0.6%, respectively, and the corresponding thermal conductivity is 0.421w (m﹒k) respectively. -1 、0.375w(m﹒k) -1 、0.498w(m﹒k) -1 and 0.552w(m﹒k) -1 .

[0067] 3. The change of thermal conductivity is related to the amount of straw added. Adding too much or too little straw is not conducive to effectively reducing the thermal conductivity.

[0068] For example, under the same other conditions, the straw addition amounts in Examples 2, 3, and 4 are 12%, 24%, and 36%, respectively, and the corresponding thermal conductivity coefficients are 0.322w (m﹒k) respectively. -1 、0.238w(m﹒k) -1 and 0.421w(m﹒k) -1 .

[0069] For another example, under the same other conditions, the straw addition amounts in Examples 6, 7, and 8 are 12%, 24%, and 36%, respectively, and the corresponding thermal conductivity coefficients are 0.289w(m﹒k) respectively. -1 、0.212w(m﹒k) -1 and 0.375w(m﹒k) -1 .

[0070] For another example, under the same other conditions, the straw addition amounts in Examples 10, 11, and 12 are 12%, 24%, and 36%, respectively, and the corresponding thermal conductivity coefficients are 0.384w (m﹒k) respectively. -1 、0.249w(m﹒k) -1 and 0.498w(m﹒k) -1 .

[0071] For another example, under the same other conditions, the straw addition amounts in Examples 14, 15, and 16 are 12%, 24%, and 36%, respectively, and the corresponding thermal conductivity coefficients are 0.401w (m﹒k) respectively. -1 、0.262w(m﹒k) -1 and 0.552w(m﹒k) -1 .

[0072] It is generally believed that as the amount of straw added increases, the apparent density of the material gradually decreases, and its thermal conductivity also decreases accordingly. However, under the premise of adopting specific component matching and specific preparation method in the present invention, when the amount of straw added is about 24%, the thermal conductivity of the material has a valley value. The main reason for this phenomenon is that under the compound combination of this formula, more uniform and closed pores are formed in the material, resulting in a lower thermal conductivity of the material.

[0073] In summary, when 24% cotton straw and 0.4% aluminum powder foaming agent are added, the maximum uniaxial compressive strength of the environmentally friendly tunnel support material is 15.5 MPa, and the thermal conductivity is 0.212 w (m﹒k) -1 It can be seen that the environmentally friendly tunnel support material under this formula has good mechanical properties and good thermal insulation properties (manifested by low thermal conductivity).

[0074] Based on the above experimental data and data direction, the present invention selects the cotton straw addition amount to be 20%~28%, and preferably 24%, and the aluminum powder foaming agent addition amount to be 0.35%~0.45%, and preferably 0.4%.

Claims

1. A method for preparing a thermal insulation reinforcement material for mine tunnel shotcrete support, characterized in that The preparation is carried out according to the following steps: first, the cotton straw is crushed, sieved, dried to a constant mass, and bagged for later use; an alkaline activator solution formed by a mixture of NaOH solution and Na2SiO3 is prepared; slag powder and fly ash are mixed and stirred to obtain a slag-ash mixture; secondly, the slag-ash mixture is mixed with the alkaline activator solution for solid-liquid mixing, and quartz sand accounting for 2-5% of the total mass of the solid-liquid mixture is added after solid-liquid mixing; after stirring, 20-28% of the total mass of the solid-liquid mixture of cotton straw, 0.35-0.45% of the total mass of the solid-liquid mixture of aluminum powder foaming agent and an appropriate amount of foam stabilizer are added in sequence; and the water-cement ratio of the water-cement ratio for the shotcrete support of the mine tunnel is prepared under stirring to be (0.4-0.6):1; the mass ratio of the slag-ash mixture to the alkaline activator solution in the solid-liquid mixture is (5-7):

1.

2. The method for preparing the thermal insulation reinforcement material for mine tunnel shotcrete support according to claim 1, characterized in that: The amount of cotton straw added is 24% of the total mass of the solid-liquid mixture.

3. The method for preparing the thermal insulation reinforcement material for mine tunnel shotcrete support according to claim 1, characterized in that: The amount of aluminum powder foaming agent added is 0.4% of the total mass of the solid-liquid mixture.

4. The method for preparing the thermal insulation reinforcement material for mine tunnel shotcrete support according to claim 1, characterized in that: The mass ratio of slag powder and fly ash is (6~8):

3.

5. The method for preparing the thermal insulation reinforcement material for mine tunnel shotcrete support according to claim 1, characterized in that The preparation method of the alkaline activator solution is as follows: 2% NaOH solution and Na2SiO3 are evenly mixed to obtain an alkaline activator solution; the mass ratio of NaOH solution to solid Na2SiO3 is (0.5~1.5):

1.

6. The method for preparing the thermal insulation reinforcement material for mine tunnel shotcrete support according to claim 1, characterized in that: The foam stabilizer is potassium stearate; the added amount is (0.04-0.06) of the total mass of the solid-liquid mixture.

7. The method for preparing the thermal insulation reinforcement material for mine tunnel shotcrete support according to claim 1, characterized in that: The quartz sand particle size is 1-4 mm.

Citation Information

Cited By

  • Mine underground wall surface structure

    CN223923049U